O projeto artístico do artesanato furioso: uma proposta de estudo da morfologia musical por meio do processo performático - Menezes, Daniel Luna de (2021)
This research aims to investigate how Artesanato Furioso develops its artistic project from an approach that places performative action as its main focus. Recognizing that the hegemonic notion of musical work would refer, according to Lydia Goehr (1992), to a musical practice arising from a specific historical and socio cultural context, which can not be applied in a generalized way, this research was based on theories of musical morphology defended by Valério Fiel da Costa (2016), which support the practice of Artesanato Furioso. In this view, the work would be situated in the morphological field, having its form concretized through performative action. The analyzes presented in this research had as main focus the performance process developed by the Artesanato Furioso project in the cases discussed. Four performances, with distinct characteristics, representing the typical situations addressed by the project were selected: Child of Tree (1975), by John Cage, Quatre Fois (1980), by Didier Guigue, Wu Li (1990), by Hans-Joachim Koellreuter, and ÍCONES: iconoclastia, iconoplasmia e o Ícone de J-P Caron (2016), from Artesanato Furioso itself. In the analysis, the interpretive decisions and solutions adopted by the performers were mapped throughout the performance process, considering, in addition to the public performances, the planning and preparation stages, and the information provided by the performers regarding their understanding of the proposed approach. From the comparison between the information and recordings collected, it was possible to trace the morphological profile of the performances studied and showing the relationship between the performance process and the morphological results produced.